Resonant-tunneling diodes with emitter prewells - Lear, Kevin L., author; Klimeck, Gerhard, author; Bowen, R. Chris, author; Boykin, Timothy B., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1999)
Resonant-tunneling diodes (RTDs) incorporating an emitter prewell structure are studied both theoretically and experimentally in order to investigate the utility of the emitter region as a device design parameter. The experiments show a tendency for peak bias, current, and the peak-to-valley ratio to increase for wider prewells, behavior likewise seen in both very simple and detailed calculations. Both the simple and more complete models point to interactions between states associated with the prewell and the main quantum well as the reasons for the increase in peak current. These results suggest design guidelines to affect peak bias, current, or the peak-to-valley ratio of RTDs.
Keywords: quantum wells; resonant tunneling diodes; barriers; emitter notch states